2022
DOI: 10.1523/jneurosci.1954-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Oligodendrocyte Maturation Is an Early Feature in SCA3 Disease Pathogenesis

Abstract: Spinocerebellar ataxia Type 3 (SCA3), the most common dominantly inherited ataxia, is a polyglutamine neurodegenerative disease for which there is no disease-modifying therapy. The polyglutamine-encoding CAG repeat expansion in the ATXN3 gene results in expression of a mutant form of the ATXN3 protein, a deubiquitinase that causes selective neurodegeneration despite being widely expressed. The mechanisms driving neurodegeneration in SCA3 are unclear. Research to date, however, has focused almost exclusively on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 56 publications
7
58
0
Order By: Relevance
“…Utilizing the versatility of Drosophila genetics along with the Gal4-UAS binary system of expression, we can express either the homomeric or the alternating polyQ repeat of pathogenic ataxin-3 transgenes individually in specific tissues [ 39 , 40 , 41 , 42 , 43 , 45 , 47 , 51 , 70 , 72 , 73 ]. We focused our investigations on the type of tissue that is primarily impacted in SCA3/MJD, neuronal and glial [ 14 , 15 , 18 , 74 ]. We used Gal4 drivers that express constructs in all neurons (elav-Gal4) or in all glial cells (except midline glia; repo-Gal4), and employed the same constructs as in Figure 1 , except that the Kozak sequences were optimized for fly-based translation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing the versatility of Drosophila genetics along with the Gal4-UAS binary system of expression, we can express either the homomeric or the alternating polyQ repeat of pathogenic ataxin-3 transgenes individually in specific tissues [ 39 , 40 , 41 , 42 , 43 , 45 , 47 , 51 , 70 , 72 , 73 ]. We focused our investigations on the type of tissue that is primarily impacted in SCA3/MJD, neuronal and glial [ 14 , 15 , 18 , 74 ]. We used Gal4 drivers that express constructs in all neurons (elav-Gal4) or in all glial cells (except midline glia; repo-Gal4), and employed the same constructs as in Figure 1 , except that the Kozak sequences were optimized for fly-based translation.…”
Section: Resultsmentioning
confidence: 99%
“…The experiments conducted in Figure 2 B,D were conducted with flies collected during development from lines expressing either construct in glia. Although we were unable to study differences in adult longevity between our two lines in glia, the high levels of toxicity in these cells compared to neurons points to an interesting role for glia in SCA3/MJD pathogenesis and is an active field of investigation; a recent study identified impaired oligodendrocyte maturation as a contributor to pathogenesis in a transgenic mouse model of SCA3/MJD [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in the brainstem, cerebellum, and spinal cord, many of the representative OL maturation transcripts were expressed at levels comparable to WT levels through 4 weeks of age ( Fig 2F-I ). Our previous study showed that changes in mature OL RNA expression translated to reduced mature OL protein expression 21 , though not until 8 weeks of age in Q84 mice. Due to the study design, we are unable to evaluate the downstream translational effects at 4 weeks.…”
Section: Resultsmentioning
confidence: 93%
“…Dysregulation in mature myelinating OL transcripts begins between 3 and 4 weeks of age in Q84 mice 21 , therefore we addressed if the onset of this impairment could be impeded with premanifest ASO treatment. Indeed, in the brainstem, cerebellum, and spinal cord, many of the representative OL maturation transcripts were expressed at levels comparable to WT levels through 4 weeks of age ( Fig 2F-I ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation